GIS Network Analysis for Volcanic Evacuation Modeling and Geography Education Frameworks - Naufal Muhammad Hanif; Syamsul Bachri (CV Bumi Spasial, 2026)
This study models optimized evacuation routes for the Kelud Volcano eruption in Blitar Regency using Geographic Information System (GIS) Network Analysis, specifically employing Closest Facility and Service Area algorithms. Utilizing disaster-prone area (KRB) maps, road network shapefiles, and evacuation post locations, the spatial simulation was parameterized based on the 2014 Kelud eruption. The model establishes a standardized empirical baseline by assuming a constant evacuation velocity of 40 km/h to estimate travel times, while acknowledging the limitations of dynamic traffic congestion during emergencies. The analysis produced two primary spatial outputs: optimal trajectories to the nearest temporary and final shelters, and comprehensive shelter accessibility isochrones. Quantitative findings indicate that evacuation distances to final shelters range from 866.4 meters (1-minute travel time) to 16,720.9 meters (25-minute travel time). While the resulting maps offer a vital spatial framework to enhance local disaster preparedness, the reliance on 2001-era road network data underscores a critical limitation. Therefore, updating regional infrastructure geospatial data is strongly recommended before integrating these models into formal disaster risk management policies to effectively minimize potential casualties and material losses.